Analysis of the use of Quick Response Code Indonesian Standard (Qris) on Parking Retribution in Mataram City - Lestari, Auliya; Sopandi, Lalu Muhamad; Rakhmawati, Intan (East Asian Journal of Multidisciplinary Research, 2024)
Quick Response code Indonesian Standard (QRIS) is a system used for non-cash payment of parking fees, one of which is in Mataram City. This study aims to determine and analyze the use of this QRIS system for parking retribution. This type of research is descriptive phenomenology with a feasibility study approach. The object of this research is QRIS of parking levy revenue in Mataram City. The results show that payment of parking retribution using QRIS is a system that is feasible to continue, and payment using a non-cash system is said to be effective because the system transition has been accepted. After using QRIS, the movement of parking levy revenue has increased, reaching a percentage of 84.74% in 2023.